Trucking wellness : an industry's response to managing HIV/AIDS - Townsend, Stephanie; Viedge, Conrad ([London] : SAGE, 2016)
In 2012, South Africa was still one of the countries with the highest prevalence of HIV/AIDS in the world. Statistics SA estimated that in 2011, 10.6% of the total population and 16.6% of the adult population (people between 15 and 49 years of age) were HIV positive. This text examines the response of the South African truck haulage industry to the challenges posed by HIV/AIDS.
Originally Published in: Townsend, S. & Viedge, C. (2012). Trucking Wellness: An Industry's Response to Managing HIV/AIDS.WBS-2012-4. Johannesburg: The Case Centre, Wits Business School.
Description based on online resource; title from home page (viewed on April 26, 2016).
Keywords: elektronické knihy; electronic books; Trucking -- Employees -- Health and hygiene -- Case studies; Employees -- Medical care -- Case studies; Trucking -- Case studies